Directive Speech Acts Analysis in Teacher and Student Interaction during Thematic Learning in Elementary School - Nisa, Lia Khoirrun; Abduh, Muhammad (LPPM Undiksha, 2022)
Directive speech acts in elementary schools are important because they are useful as a form of pragmatic scientific study that can enrich the development of pragmatics in elementary schools. The purpose of this study is to analyze the forms of directive speech acts used by teachers and to describe the strategies of directive speech acts of teachers and students during the learning process. This study uses a qualitative approach. The method used in this research is using descriptive qualitative method with data collection techniques, namely using observation techniques, recording techniques, listening and noting. The subjects in this study were teachers and students at public elementary schools who were observed during the learning process. To prove the suitability of the data using triangulation. The result of this research is that during the learning process, the teacher uses various kinds of directive speech acts which are quite good. The directive speech act used by the teacher is the question directive speech act. In addition, the teacher's most dominant directive speech act strategy is the directive speech act strategy of speaking frankly without further ado.